PEMBUATAN PROTOTIPE ALAT PENDETEKSI LEVEL AIR MENGGUNAKAN ARDUINO UNO R3 - sofyan sofyan; Catur Budi Affianto; Surliyan Surliyan (Informasi Interaktif, 2016)
The prototype of this water level detector uses the Arduino Uno R3 Microcontroller based on the ATmega328P chip to detect the water level. For the output of its arduinonya connected to the LED light (light), the busser (sound) and serial are connected to the laptop to display the readings from the water level, whether the water level is safe or dangerous.Key words: water level, arduino, microcontroller